2001
DOI: 10.1080/02791072.2001.10400573
|View full text |Cite
|
Sign up to set email alerts
|

Self-Help Group Meeting Attendance among Clients with Dual Diagnoses

Abstract: This study explores factors associated with self-help group meeting attendance in the aftercare of 81 clients with dual diagnoses of severe mental illness and chemical dependency following their discharge from an inpatient chemical dependency treatment program. It also explores the association between self-help group meeting attendance and treatment outcomes. Data were collected from patient records and results of the Addiction Severity Index (ASI) administered as part of an earlier experiment that evaluated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…In one study, after discharge from hospital, dually diagnosed patients attended 12 step groups about as often as patients with substance disorders only, although patients with schizophrenia and schizoaffective disorder attended least (Jordan et al, 2002). Two studies have reported higher rates of mutual aid attendance among dually-diagnosed persons than have previously been indicated in the literature (DiNitto et al, 2001;Bogenschutz & Akin, 2000). However, both of these studies also raised questions about the effective use of traditional 12-step fellowships by this population.…”
Section: "Traditional" Mutual Aid and Dually Diagnosed Personsmentioning
confidence: 66%
See 2 more Smart Citations
“…In one study, after discharge from hospital, dually diagnosed patients attended 12 step groups about as often as patients with substance disorders only, although patients with schizophrenia and schizoaffective disorder attended least (Jordan et al, 2002). Two studies have reported higher rates of mutual aid attendance among dually-diagnosed persons than have previously been indicated in the literature (DiNitto et al, 2001;Bogenschutz & Akin, 2000). However, both of these studies also raised questions about the effective use of traditional 12-step fellowships by this population.…”
Section: "Traditional" Mutual Aid and Dually Diagnosed Personsmentioning
confidence: 66%
“…DTR provides an opportunity for dually diagnosed patients to receive peer support for taking prescribed psychiatric medication, which can be as crucial for recovery as abstinence from drugs and alcohol. However, DTR is not conceptualized as a replacement for traditional 12-step groups, which are also attended by many dually diagnosed persons despite their limitations (e.g., DiNitto, et al, 2001), but rather as serving a special need for peer support that otherwise would not be met. As noted in the Double Trouble in Recovery (1998) Manual, "DTR creates a safe environment where a person can discuss the issue of mental disorders, medication, medication side-effects, psychiatric hospitalizations and experiences with the mental health system openly without shame or stigma."…”
Section: Description Of Double Trouble In Recoverymentioning
confidence: 99%
See 1 more Smart Citation
“…Two exceptions were found to this general pattern. One study reported no association between 12‐step attendance and improvement in ASI scores (other then legal problems) (Dinitto et al., 2001). Another found a smaller effect of 12‐step on substance use in patients with major depression and substance use disorder than in patients with substance use disorder alone (Kelly et al., 2003) .…”
Section: Resultsmentioning
confidence: 99%
“…Psychiatric comorbidity was not a significant predictor of self‐help group participation, and patients with a history of psychosis were excluded from this study. Dinitto et al explored the characteristics associated with self‐help participation among 81 dually diagnosed patients 23 . Only two of the thirteen factors investigated were associated with increased use of self help: higher education level and a major substance abuse problem that did not include alcohol.…”
Section: Resultsmentioning
confidence: 99%